2013
DOI: 10.1016/j.echo.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Three-Dimensional Myocardial Strain Estimation Using Echocardiography

Abstract: With the developments in ultrasound transducer technology and both hardware and software computing, real-time volumetric imaging has become widely available, accompanied by various methods of assessing three-dimensional (3D) myocardial strain, often referred to as 3D speckle-tracking echocardiographic methods. Indeed, these methods should provide cardiologists with a better view of regional myocardial mechanics, which might be important for diagnosis, prognosis, and therapy. However, currently available 3D spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 79 publications
3
113
0
1
Order By: Relevance
“…3D-STE as a novel echocardiographic technique has allowed advances in comprehensive evaluation of cardiac mechanical movement among various clinical scenarios [21][22][23][24]. Furthermore, one of the particular advantages of 3D-STE is the improved accuracy of LV twisting measurements [25,26]. This study showed feasibility and reproducibility of 3D-STE in assessment of early changes in LV twisting function in patients with lymphoma exposed to anthracycline.…”
Section: Discussionmentioning
confidence: 79%
“…3D-STE as a novel echocardiographic technique has allowed advances in comprehensive evaluation of cardiac mechanical movement among various clinical scenarios [21][22][23][24]. Furthermore, one of the particular advantages of 3D-STE is the improved accuracy of LV twisting measurements [25,26]. This study showed feasibility and reproducibility of 3D-STE in assessment of early changes in LV twisting function in patients with lymphoma exposed to anthracycline.…”
Section: Discussionmentioning
confidence: 79%
“…STE is based on tracking speckle patterns in conventional B-mode images, which is now feasible using readily available computational resources. Yet, in spite of its popularity, attested by thousands of clinical echocardiographic studies [8][9][10][11][12][13] over the last 10 years, translating STE into the daily clinical routine is far more challenging in both the single and multi-vendor clinical environments. Thus, though the Strain Standardization Initiative reduced significantly the inter-vendor variability of the strain measurements, a consequent study [14] concludes that current vendor independent STE software do and the sam Speckle tracking is mostly performed by block-matching [19][20][21][22] , where the displacement of a material point is estimated by searching for the "best match" between a block in the source frame and a block in the target frame.…”
Section: Introductionmentioning
confidence: 99%
“…The segmentation of left ventricular (LV) boundaries on echocardiography images is especially difficult. Echocardiography is one of the major imaging techniques to measure the heart functions [6]. The detection of the cardiac boundaries, especially left ventricular (LV) boundaries on echocardiography images, is crucial for the quantitative cardiac functional assessment.…”
Section: Introductionmentioning
confidence: 99%